Sulfonamide-salicylaldehyde imines active against methicillin- and trimethoprim/sulfonamide-resistant Staphylococci - Krátký, Martin; Konečná, Klára; Janoušek, Jiří; Janďourek, Ondřej; Maixnerová, Jana; Kalivodová, Sára; Trejtnar, František; Vinšová, Jarmila (Future medicinal chemistry, 2021)
Background: Increasing resistance has resulted in an urgent need for new antimicrobial drugs. A systematic me-too approach was chosen to modify clinically used sulfonamides to obtain their imines. Methods & results: Twenty-five compounds were synthesized and evaluated for their antibacterial activity. The most active compounds were also investigated against methicillin- and trimethoprim/sulfamethoxazole (SMX)-resistant Gram-positive species. Staphylococci shared the highest susceptibility including resistant strains with minimum inhibitory concentrations from 3.91 μM (≥2.39 μg ml-1). Crucially, the compounds inhibit MRSA and trimethoprim/SMX-resistant Staphylococci without any cross-resistance. Modification of parent sulfonamides turned a bacteriostatic effect into a bactericidal effect. Toxicity for HepG2 and hemolytic properties were also determined. Conclusions: The presence of a dihalogenated salicylidene moiety is required for optimal activity. Based on toxicity, promising derivatives for further investigation were identified.
Keywords: molekulární struktura; sulfonamidy; aldehydy; Microbial Sensitivity Tests; iminy; mikrobiální testy citlivosti; drug resistance; Staphylococcus aureus; Imines; sulfonamides; Anti-Bacterial Agents; antibacterial activity; Molecular Structure; cytotoxicity; bakteriální léková rezistence; Drug Resistance, Bacterial; sulfamethoxazole; in vitro activity; imine; Sulfonamides; Staphylococcus; Schiff bases; Aldehydes; antibakteriální látky